The Immaterial Heritage in the Iraqi Contemporary Painting: Holy Najaf as a Sample - Al-Yasiri, Saba Qais (Journal of Humanities & Social Sciences, 2022)
The present study aims at identifying the immaterial heritage in the Iraqi contemporary painting reflected in the paintings of the Najafi painters. The statement of the problem can be put in the following research questions: what are the immaterial heritage implications in the Holy Najaf painters? What are the representations and reflections of the immaterial heritage in the paintings? Thus, the study hypothesizes that: 1. The religious reality of Najaf is an immaterial heritage that can be represented in painting. 2. Heritage can be affected by social traditions and affects the individuals of the community. After introducing the previous studies, the theoretical background of the study has included the following: introducing the Iraqi contemporary painting, an introduction to the immaterial heritage, and studying certified interviews with some painters of the Holy Najaf. As for the procedures followed in the study, a sample of the paintings of thirteen painters, as a representation of the population of the study, were investigated to identify the the works that were believed to show the immaterial heritage. Using observation as a research tool and depending on the indications found in the theoretical background, the researcher has designed an analytical form to reach at the following findings: 1. Features of the immaterial heritage like traditions and religious rituals have shown up to be a compressive structure of the paintings of the Najafi painters. This verifies the first hypothesis. 2. The environment and heritage leave traces of symbols that make the contemporary painting full of heritage as an effective factor. This verifies the second hypothesis. In addition, there have been some conclusions like: 1. The immaterial heritage in the paintings of the Najafi painters is realized by features related to Shiite Doctrine. 2. The Najafi religious environment was reflected in items and symbols loaded with local merits. The study has then come to end with some recommendations concerning the study of the immaterial heritage in the Arab contemporary painting in addition to its effect on the Arab identity.